RANCANGAN PEMBELAJARAN MATEMATIKAMENGGUNAKAN PETA LOKAL RIAU - Alfiah, Nurul; Roza, Yenita; Maimunah, Maimunah (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: The background of this research is the lack ofteaching materials that introducedregionalresourcesto studentsin accordance with the demands of 2013 curriculum.This Research aims to develop teaching materials in the form of books that introduce regional wealth to students by introducing the map of Riau.This Research is a research and development (R&D) using the 4-D model that consist of define, design, develop and dissemination.These research conducted by researchers until the design stage.The research instrumentis validity instruments is a form of a validation sheet to assess the feasibility of the teaching materialsand practicality instruments is a form of a questionnaire for students responses to teaching materials.KeyWords: Mathematics Learning, Maps of Riau, 4-D Development Model.